2016
DOI: 10.1177/1352458516679267
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell subpopulations are associated with MRI activity in a relapsing-remitting multiple sclerosis patient cohort from Australia

Abstract: The independent association of NK subsets with MRI stability needs to be confirmed in prospective studies to test their usefulness in predicting disease activity in MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
6
23
0
Order By: Relevance
“…Our results support previous findings that peripheral blood from people with MS has fewer CD56bright NK cells than HC [4]. Other findings have been reported; CD56bright NK cells were increased in blood from people with RRMS with no disease-associated MRI changes over 2.4 years [5]. CD56 bright NK cells can have multiple functions, including production of cytokines such as IFN-γ, IL-10 and TNF-β, as well as cytotoxic and regulatory activities in T cell responses [5,6].…”
Section: Discussionsupporting
confidence: 92%
“…Our results support previous findings that peripheral blood from people with MS has fewer CD56bright NK cells than HC [4]. Other findings have been reported; CD56bright NK cells were increased in blood from people with RRMS with no disease-associated MRI changes over 2.4 years [5]. CD56 bright NK cells can have multiple functions, including production of cytokines such as IFN-γ, IL-10 and TNF-β, as well as cytotoxic and regulatory activities in T cell responses [5,6].…”
Section: Discussionsupporting
confidence: 92%
“…NK bright and invariant NKT cells, a subset of NKT, are often related to regulatory processes ( 46 ). In MS patients, a high proportion of NK bright cells has recently been associated with stable MRI ( 47 ), and we found that a higher percentage of these cells before treatment was associated with a good response and that they decreased to a lesser degree after treatment in responder compared with NR patients. In our study, fingolimod not only increased the percentage of NK cells but it also upregulated NCAM1 (CD56) and FCGR3A (CD16a) at the transcriptional level; an enrichment of the NK and innate response pathways was also observed as a result of the therapy.…”
Section: Discussionsupporting
confidence: 51%
“…The deep profiling of NK cells performed here, including in the placebo group, can also serve as a reference for future studies of NK cell phenotype in the setting of RMS. While daclizumab beta was voluntarily withdrawn from the market due to serious adverse events, it is notable that several other medications used to treat RMS, including natalizumab, fingolimod, glatiramer acetate, or beta interferon, are also associated with expanded CD56 bright NK cells in the setting of clinical response (53). Thus, in order to improve treatment for RMS, it will be critical in future studies to determine whether specific features of NK cells are associated with clinical response or serious adverse events.…”
Section: Discussionmentioning
confidence: 99%